THE ROLE AND SIGNIFICANCE OF THE ESTABLISHMENT OF THE NEW BRICS DEVELOPMENT BANK - Marjanovic, Boban; Kraktus, Ema (Serbian political thought, 2025)
Establishing the New Development Bank by the BRICS countries (Brazil, Russia, India, China, and the Republic of South Africa) represents a strategic step toward building an alternative financial institution that promotes equality, multipolarity, and sustainable development. This paper aims to analyze the role and significance of the NDB’s founding within the context of the global economic architecture, with particular emphasis on the Bank’s decision-making mechanisms, institutional structure, and strategic priorities. The study juxtaposes the NDB with existing multilateral financial institutions such as the IMF and the World Bank through desk analysis and comparative methodology, highlighting key differences in governance models and power distribution. A normative structural analysis provides insight into how the NDB functions as an instrument of economic emancipation for developing countries and as a platform for financing infrastructure and sustainability projects. The paper concludes that the New Development Bank is not merely a financial alternative but also a symbol of a new approach in international relations that aspires toward a more equitable global distribution of resources and influence.
Keywords: BRICS; New Development Bank; global governance; multipolarity; economic cooperation; infrastructure financing; international institutions